Pre-hospital delays among patients with acute coronary syndrome in the Russian Federation: a multicentre prospective observational cohort study (the AMIR Study) - Bates, Katie; Schirmer, Henrik; Kontsevaya, Anna; Bobrova, Natalia; Leon, David A.; McKee, Martin (Frontiers in Disaster and Emergency Medicine, 2023)
To describe total pre-hospital delays (symptom onset to admission), patient delay (symptom onset to calling for help), and transport delay (calling for help to admission) experienced by patients with acute coronary syndrome (ACS) in Russia and to identify factors associated with longer delays.A prospective observational cohort study of ACS patients with myocardial infarction recruited in hospitals providing percutaneous coronary intervention (PCI) and those that do not (non-PCI) in 13 regions and at multiple levels of the health system in Russia. Data were collected on prehospital delay between symptom onset and admission to the hospital providing definitive treatment, divided into patient delay (time between symptom onset and calling for help) and transport delay (time between calling for help and admission).701/902 (77.7%) patients had full data on pre-hospital delays. Median total prehospital delays in our study was 5.1 hours, median patient delay was 1.5 hours and median transport delay was 2.1 hours. Patient delay did not differ by age and sex, although having a STEMI and certain symptom presentations, including severe pain, reduced delays. Transport delays were markedly reduced in those transported by Emergency Medical Services (EMS) and taken directly to the hospital of definitive treatment (rather than one closer but unable to offer PCI). Whilst transport delays were reduced in those using EMS, just half of patients using EMS had a transport delay of less than 2 hours (first medical contact to admission). Among all patients taken directly to hospital by EMS, 70% were STEMI patients. Of these STEMI patients, 78% had a transport delay of 2 hours or more. Among these patients, only 16.0% received thrombolysis in the ambulance. As expected, regional differences were apparent with all types of delay, with greatest variation found in transport delays. Delays are currently longer than European Society of Cardiology guidelines for STEMI patients and other severe cases., Reducing patient delay will reduce overall delays. Transport delays are inevitable in many regions of Russia but better triage of patients, increased use of EMS, and early thrombolysis in EMS, particularly for STEMI patients facing excessive transport delays, will reduce delays and buy time before PCI.